Analisis Semiotika Charles Sanders Peirce pada Lukisan Seri Ilham Karim - Krisna Ramadhan; Slamet Supriyadi (Universitas Palangka Raya, 2025)
The purpose of this research is to analyze the meaning of Ilham Karim's series of paintings Butterflies In My Stomach through Charles Sanders Peirce's semiotic approach. This research analyses the semiotic process in Karim's 12-painting series, which depicts the emotional journey of his parents' relationship in three phases: encounter, conflict and separation. This research uses qualitative methods through structured interview and literature review. The results of the analysis using Peirce's semiotics show that visual signs such as the consistent use of sofa objects, bright colors and uniquely packaged figure gestures represent harmony, conflict and loss. The triadic interpretation (representament, object and interpretant) reveals a profound message about the emotional dynamics of family relationships. The results of this research provide a new understanding of visual symbolism in contemporary art world, particularly in the context of identity expression and personal trauma.